The role of community health workers in enhancing home and community-based services in American Indian communities - Zavera K. Basrai; Caroline Y. Yoon; Valerie Tsosie; Ronny A. Bell; Nathan A. Boucher (PEC Innovation)
Objectives: Describe the role and benefit of Community Health Workers in American Indian communities as a novel solution to meeting home and community-based service (HCBS) needs. Methods: Short communication based on extant literature and current policy challenges. Results: Community health workers (CHW) play an essential role in various healthcare settings particularly in American Indian (AI) communities working to close gaps in preventive and comprehensive healthcare accessibility. CHWs close these gaps through providing expertise in culturally oriented and familial support, educating communities on acute and chronic illnesses and wellness, and dispelling misinformation regarding health issues. However, integration and application of CHWs into home- and community-based services has limited recognition and utilization in healthcare systems and healthcare payment. Robust training/credentialing pathways and sustainable funding streams are essential for the integration of CHWs into the formalized healthcare provider team. Barriers that prevent this integration include inconsistencies in documentation, lack of stable funding, and a lack of formal professional recognition. Conclusions: Previously successful models of CHW integration promote formalized training programs, professional development opportunities, earning certifications, and promoting collaboration between CHWs and providers. Innovation: Applying CHW use in HCBS can increase community wellness while mitigating impacts of health disparities in HCBS for an often-under-resourced set of communities – our nation's American Indian communities.